(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
As of late, the incessant coal mine security mischances have brought on genuine obstructions and huge monetary misfortunes. It has given high essentials to avoid the underground complications within the mines with better improved in the mine security aspects. In this paper, GSM operated Wireless Sensor (WS)based mine security and safety methodology is presented.Different conditions within the mine have been considered including mine temperature, humidity, Oxygen monitoring, smoke and CO2 levels and so on with control actions. All these conditions are monitored and controlled with the use of WS grids.Remote hubs are allotted for every sensor so that wireless data transmission alongside telemetry applications has been carried out.